(untitled) (Journal of Bangladesh Academy of Sciences, 2022)
The adsorption of methylene blue (MB) was investigated using the prepared activated carbon (AC); obtained by the chemical activation of chrome shaving dust (CSD). Results represented that the increase of particle size and impregnation ratio of AC possessed a proportional effect on the adsorption of MB. AC produced by H3PO3, impregnation ratio of 1:6, and mesh size of 40 showed the highest adsorption performance. The removal of other organic and inorganic pollutants from different tannery effluent was found satisfactory like pH, conductivity, turbidity, BOD5, COD, and Cl- values are reduced to 5.5- 8.48, 73-93%, 76-92%, 80-96%, 71-87% and 84-94%, respectively which are nearly closed to the WHO’s standards for industrial effluent to the environment. The microscopic analysis confirmed the smooth and porous surface characteristics of the adsorbent. Hence, CSDAC can be expected to become an effective, low-cost, and suitable adsorbent for both dye and pollutants removal from industrial wastewater. J. Bangladesh Acad. Sci. 46(1); 75-83: June 2022